Deliberate ignorance : choosing not to know - Hertwig, Ralph; Engel, Christoph, 1956- (Cambridge, Massachusetts : The MIT Press, 2020)
"Psychologists, economists, historians, computer scientists, sociologists, philosophers, and legal scholars discuss when is deliberate ignorance a virtue, and what type of environment does it require"--
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Ignorance (Theory of knowledge) -- Social aspects; Ignorance (Theory of knowledge) -- Psychological aspects